ANALISIS STABILITAS BENDUNGAN URUGAN TANAH: UJI MODEL FISIK DI LABORATORIUM DAN ANALISIS ELEMEN HINGGA - , HELMI FUADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The dam with the great benefits, also keeps the potential dangers that can make to disaster if the operation and maintenance not done well. Some conditions that considered unstable and may lead to the collapse or dam failure on the structure is the fluctuation of water level with great intensity but in a short period. Soil dam collapse mechanism is also very concerned with the interaction of water level fluctuations with the material of soil dam body. This research analyzed the influence of the fluctuation of water level to the deformations and the stabilities of soil dam. Physical model of soil dams built inside a drainage and seepage pool. Model of soil dams constructed by 2 variations of upstream slope are 1:1 and 1:1.5 with the composition of body material are 10% sandy silt and 90% sand (called T10P90), 20% sandy silt and 80% sand (called T20P80) and 100% soil (called T100). The value of deformation and stability of experimental results compared with numerical simulation results using finite element method by PLAXIS programs version 8.5. Experimental results and numerical simulation showed the deformation and stability of dam model more affected by the height of water level. The higher the water level, the greater the deformation happens and stability decrease. The smallest of Safety Factor (SF) is 1,027 occurred on the model T10P90 with upstream slope 1:1 (called T10P90-S1:1) on the conditions of rising water level, amounted to 1,331 on T10P90-S1:1 at rapid rising of water level condition and amounted to 1,051 on T10P90-S1:1 at rapid drawdown condition. The largest SF occurred in model T100-S1:1 by 1,680 at rising of water level condition, amounted to 1,944 on T100-S1-1,5 at rapid rising of water level, and 1,695 on the model T100- S1:1 at rapid drawdown condition. SF on T100 model is more safety rather than T20P80 and T10P90. It means the dam model with more of soil is more safety rather than the dam model with more of sand.